Respostas
respondido por:
2
y = - (-3)² + 6.(-3) - 9
y = - 9 - 18 - 9
y = -36
y = - (-1)² + 6.(-1) - 9
y = - 1 - 6 - 9
y = -16
y = - (0)² + 6.(0) - 9
y = -9
y = - (1)² + 6.(1) - 9
y = - 1 +6 - 9
y = 6
y = - (3)² + 6.3 - 9
y = - 9 + 18 - 9
y = 0
y = - 9 - 18 - 9
y = -36
y = - (-1)² + 6.(-1) - 9
y = - 1 - 6 - 9
y = -16
y = - (0)² + 6.(0) - 9
y = -9
y = - (1)² + 6.(1) - 9
y = - 1 +6 - 9
y = 6
y = - (3)² + 6.3 - 9
y = - 9 + 18 - 9
y = 0
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás